The Effect of Metabolic Diseases on the Outcome of Bevacizumab Injection for Central Serous Retinopathy - M Babaei; H Shirafkan; SA Rasoulinejad (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2022)
Background and Objective: Central serous retinopathy (CSR) is an idiopathic retinal disease that causes visual impairment and metamorphopsia. Due to the unknown etiology of CSR, the present study was conducted to investigate the role of metabolic disorders such as hyperlipidemia, diabetes, hypothyroidism, and hypertension (as a cardiovascular disease) in the treatment outcome of CSR patients. Methods: This cross-sectional study was performed on 55 CSR patients whose problem was approved by ophthalmologic examinations in the Ophthalmology center of Ayatollah Rouhani Hospital, Babol, Iran. The patients were then treated with intravitreal injection of 1.25 mg/0.05 ml bevacizumab (Avastin®) 3 to 4 millimeters away from limbus under sterile conditions. Based on having and not having hypertension, diabetes, hypothyroidism and obesity, all patients underwent ophthalmological examination, including visual acuity (VA) and central macular thickness (CMT) by optical coherence tomography (OCT) before injection and one month after that. Findings: The mean age of CSR patients (32 men and 23 women) was 42±11.50 years. After treatment, the CMT value in hypertensive patients (328.66±34.00 µm) was significantly higher than non-hypertensive patients (302.56±41.79) (p=0.025). The CMT value after treatment was considerably lower in non-diabetic patients (306.08±42.49 µm) compared to diabetic patients (336.77±17.42 µm) (p=0.039). Neither VA nor CMT was significantly different between hyperlipidemic patients and non-hyperlipidemic patients. In addition, there were no significant differences in VA and CMT between patients with hypothyroidism and without hypothyroidism. Conclusion: The results of this study showed that hypertension and diabetes are important factors in CSR patients’ response to bevacizumab injection.